Chitosan and cyanoguanidine-crosslinked chitosan coated glass beads and its application in fixed bed adsorption. Issue 11 (2nd November 2019) - Vieira, Mery L. G.; Pinheiro, Cláudio P.; Silva, Keli A.; Lutke, Sabrina F.; Cadaval, Tito Roberto Sant' Anna; Dotto, Guilherme; Pinto, Luiz Antonio de Almeida
Abstract: The aim of this work was to coat glass beads with chitosan and cyanoguanidine-crosslinked chitosan and, afterward, to verify the potential of the coated beads as adsorbent for the FD&C Red 40 dye in fixed bed column. The coating was realized in eight experimental conditions, varying the technique (dip coating or casting) and the coating solution composition (different proportions of chitosan, cyanoguanidine, glycerol, sorbitol, sodium alginate, NaOH and CaCl2 ). The beads coated in the eight experimental conditions were then applied to adsorb FD&C Red 40 in a fixed bed column, from aqueous solutions at pH 3.0 and 6.0. The breakthrough curves were fitted according to Thomas and Yoon-Nelson dynamic models. The coating was dependent of the solution composition. The casting technique presented coating percentage values of 92%, while the dip coating technique presented only 43%. The breakthrough curves revealed that the use of glass beads coated with cyanoguanidine-crosslinked chitosan had good performance, attaining adsorption capacity values higher than 80 mg g −1 . Thomas and Yoon-Nelson models were able to predict the breakthrough curves in all conditions.